The Influence of Principal’s Leadership and Teachers’ Work Discipline on Junior High School Teachers’ Performance - Rahmadini, Miranda Ayu; Lian, Bukman; Fahmi, Muhammad (PPSDP International Journal of Education, 2025)
This study aims to investigate and clarify: (1) The influence of principle leadership on teacher performance; (2) The influence of teacher work discipline on teacher performance; and (3) The combined influence of principal leadership and teacher work discipline on teacher performance. With 57 teacher respondents, this research was conducted at State Junior High Schools located in the Buay Pemuka Peliung and Buay Madang District. The approach of data collection uses surveys, records, and interviews. Content validity and construct validity are among the validity tests. Cronbach’s Alpha is used in the reliable evaluation. Using the normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test, the preliminary evaluation of the research finds Both multivariate and simple linear regression techniques were used on the data. The findings of the research showed that: (1) the leadership of the principle affected teacher performance; (2) teacher work discipline affected teacher performance; and (3) both the principal’s leadership and teacher work behaviour taken together shaped teacher performance.